Characterization of Bombyx mori nucleopolyhedrovirus Bm17. (7th September 2012) - Shen, Hongxing; Wang, Rudu; Han, Qinggong; Zhang, Wen; Nin, Bin; Zhou, Yang; Shao, Shihe; Yao, Qin; Chen, Keping; Liu, Xiaoyong
<x xml:space="preserve">Abstract</x> Open reading frame17 (Bm17) of Bombyx mori nucleopolyhedrovirus is a highly conserved gene in lepidopteran nucleopolyhedroviruses, suggesting that it performs an important role in the virus life cycle whose function is unknown. In this report, we describe the characterization of Bm17. Reversed transcriptive‐PCR (RT‐PCR) and Western blot analysis demonstrated that Bm17 was expressed as a late gen. Immunofluorescence analysis by confocal microscopy showed that BM17 protein was localized on cytoplasm and nucleus of infected cells. These results show that BM17 was a late protein localized in cytoplasm and nucleus.